The Transmission Mechanism of Indonesia’s 1997-1998 Monetary Crisis: An Integrated Analysis of Exchange Rate Dynamics, Monetary Policy, and the Financial System - Mawardi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The 1997-1998 monetary crisis in Indonesia was a complex economic event that requires an in-depth understanding of intersectoral linkages. This study aims to analyze the transmission mechanism of the crisis through the interaction between the exchange rate, monetary policy, and the financial system. The method employed is a qualitative approach using descriptive-analytical techniques applied to secondary data from the 1997-1998 period. The findings show that the sharp depreciation of the rupiah triggered a domino effect, leading to a surge in inflation and forcing the implementation of tight monetary policy through an extreme increase in interest rates. The novelty of this study lies in the reconstruction of the crisis transmission path by integrating three sectors simultaneously foreign exchange, monetary policy, and banking within a chronological narrative in order to reveal how exchange rate shocks systematically evolved into financial system failure. These findings confirm the existence of an interconnected crisis transmission mechanism, in which instability in one variable was able to paralyze the entire national economic system in a multidimensional manner.